Effects of Parental Incarceration: A Grandparent's Perspective - Mast, Cosette J (2022)
This qualitative study explored grandparents’ perceptions of parental incarceration effects on the grandchildren they are raising. Children of incarcerated individuals are directly affected by the high incarceration rate in the United States and often find themselves displaced from the people and environment they know. As one of the most common caregivers for children with incarcerated parents, grandparents offer a unique perspective on the effects that parental incarceration has on children. The study found that grandparents perceive that the effects of parental incarceration on children are diverse. Children represented in the study were negatively affected emotionally and behaviorally by parental incarceration, displacement, and associated traumas, yet placement with a grandparent during periods of parental incarceration had positive effects on child outcomes. Grandparents indicated a need for external support, more of a voice, and a more efficient process for kinship care. To be most effective, social workers who encounter children and grandparents affected by parental incarceration should take time to carefully understand the unique effects of parental incarceration on the child, being careful not to assume that a child has been impacted by parental incarceration in any way